Billing for pacemakers and electrophysiological procedures - Stanley, Anthony (SA Heart Journal, 2017)
Due to the rapid expansion of electrophysiological procedures, fee structures have become complex. In order to simplify this structure it is proposed that fees be charged on a per-procedure basis. This will result in a better system less prone to inappropriate use. It will also aid funding of the procedures with a smaller chance of a ballooning cost for that procedure. A degree of risk sharing will make procedures more streamlined.